Spirituality in Adult Education: From the Voices of Educators and Learners - Bradley C. Courtenay; Judy Milton (Adult Education Research Conference, 2004)
Three components of spirituality were identified by adult educators and learners: sense of connectedness, search for meaning, and awareness of a transcendent force. Integrating spirituality into practice focused on the belief that spirituality is present in each of us and adult education provides an opportunity to experience it.